2016
DOI: 10.3390/ijerph13111076
|View full text |Cite
|
Sign up to set email alerts
|

Combined and Relative Effect Levels of Perceived Risk, Knowledge, Optimism, Pessimism, and Social Trust on Anxiety among Inhabitants Concerning Living on Heavy Metal Contaminated Soil

Abstract: This research aims at combined and relative effect levels on anxiety of: (1) perceived risk, knowledge, optimism, pessimism, and social trust; and (2) four sub-variables of social trust among inhabitants concerning living on heavy metal contaminated soil. On the basis of survey data from 499 Chinese respondents, results suggest that perceived risk, pessimism, optimism, and social trust have individual, significant, and direct effects on anxiety, while knowledge does not. Knowledge has significant, combined, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Although the Superfund program is intended to reduce public health risks and improve living conditions, residents have also developed negative emotional responses towards hazards and the decision-makers associated with the program (e.g., [ 72 , 73 , 74 ]). Fears of stigmatization and concerns about economic development have long been associated with how people cope with risk in mining-impacted communities [ 73 , 75 ]. Baxter and Lee [ 76 ] found that a strong sense of community pride and a fear of stigmatization prevented people from outwardly expressing concern about the health risks of a nearby hazardous waste facility.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Superfund program is intended to reduce public health risks and improve living conditions, residents have also developed negative emotional responses towards hazards and the decision-makers associated with the program (e.g., [ 72 , 73 , 74 ]). Fears of stigmatization and concerns about economic development have long been associated with how people cope with risk in mining-impacted communities [ 73 , 75 ]. Baxter and Lee [ 76 ] found that a strong sense of community pride and a fear of stigmatization prevented people from outwardly expressing concern about the health risks of a nearby hazardous waste facility.…”
Section: Discussionmentioning
confidence: 99%
“…As previously established, trust in other people (friends, acquaintances, strangers, etc.) is related to lower anxiety levels in various health-threatening situations ( Delhey and Newton, 2003 ; Tang et al, 2016 ). An explanation of this finding might be related to the fact that persons with a higher trust in other people may perceive a lower level of risks related to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…People with higher education may also be more concerned about national development and social stability, which may make them vulnerable to anxiety during epidemic outbreaks. Many studies have revealed that highly educated individuals tend to suffer from "knowledge anxiety" [45,46]. Furthermore, anxiety can develop into behavioral changes such as constantly disinfecting and scrambling for medicines.…”
Section: Discussionmentioning
confidence: 99%